To Caesar What Is Caesars: Tribute, Taxes, and Imperial Administration in Early Roman Palestine - Udoh, Fabian E. (Brown Judaic Studies, 2020)
In this book, Fabian E. Udoh offers an exhaustive study of all the sources relating to taxation in Roman Palestine. Udoh concludes that by the standards of the Roman Empire, taxation in Palestine was not oppressive. This has implications for thinking about the environment in which Jesus functioned; the cause of the Jewish Revolt (66 CE - 70 CE); and Roman taxation generally.